1985
DOI: 10.1002/kin.550171202
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study for the reactions of OH radicals with dimethylsulfide, diethylsulfide, tetrahydrothiophene, and thiophene

Abstract: The reactions of OH radicals with dimethylsulfide (DMS) diethylsulfide (DES), tetrahydrothiophene (THT), and thiophene have been studied at room temperature for DES and THT, a t 273,293, and 318 K for DMS, and at 293 and 318 K for thiophene by the discharge flow EPR technique in a halocarbon wax coated reactor. The following rate constants were obtained a t room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Hence, the oxidation reactions of this compound are the most extensively studied amongst all reduced sulfur compounds. The rate coefficient for the reaction of OH with CH3SCH3, which is believed to initiate the oxidation, has been measured using various methods and the results obtained are tabulated in [67]. As noted by Wine et al [25], the reasons for the higher numbers by Atkinson et al [33] and Kurylo [64] are probably due to the presence of either CH3SH or CH3SSCH3 in the CH3SCH3 samples.…”
Section: Oh + Ch3sch3 -Products; K5mentioning
confidence: 98%
“…Hence, the oxidation reactions of this compound are the most extensively studied amongst all reduced sulfur compounds. The rate coefficient for the reaction of OH with CH3SCH3, which is believed to initiate the oxidation, has been measured using various methods and the results obtained are tabulated in [67]. As noted by Wine et al [25], the reasons for the higher numbers by Atkinson et al [33] and Kurylo [64] are probably due to the presence of either CH3SH or CH3SSCH3 in the CH3SCH3 samples.…”
Section: Oh + Ch3sch3 -Products; K5mentioning
confidence: 98%
“…OH: Atkinson et al (1977) Wine et al (1981), Wine et al (1984), Wine (1987) Baulch et al (1984), Martin et al (1985) Wallington et al (1986a, Nielsen et al (1986), Hynes et aI. (1986), Hsu et&.…”
Section: Referencesmentioning
confidence: 99%
“…The values for the rate coefficients for the HO + CH3SCH 3 reaction obtained by Wine et al [20], Wallington and Atkinson [24] and Martin et al [28] are about a factor of 2 lower than obtained by others. However, in a private communication, Wine reports that the rate coefficient increases from (4.6 ± 0.3) x 10 "12 cm3/molec./s in the absence of 02 to (6.3 ± 0.5) x 10 -12 cm3/molec./s in 1 atm of 02 .…”
Section: S Ss S Osmentioning
confidence: 69%
“…Six studies have been reported for the measurement of the rate coefficient of HO with thiophene and they are given in Table III. The earlier discharge flow studies [32,33] agree with each other but are about a factor of 5 higher than the other studies, three of which were done by flash photolysis and one of which [28] was a redetermination of the value of Macleod et al [33] done in LeBras'…”
Section: S Ss S Osmentioning
confidence: 74%
See 1 more Smart Citation